Postnatal Growth Restriction Is Reduced If Birth Weight Is Used for Nutritional Calculations in ELBW Infants - Pradeep Alur; Harithsa Asuri; Jane Cirelli; Ankita Patel; Theodore Bell; Jonathan Liss; Naveed Hussain (International Journal of Pediatrics)
Since fluid and nutrition needs and delivery in ELBW infants are calculated based on their body weights, there could be a measurable difference in fluid, nutrition, and protein intake calculations based on birth weight (BW) or current weight of the infant, especially in the first two weeks of life. Theoretically, the use of current daily weight (CW) for calculations may result in decreased fluid, nutrition, and protein delivery as well as a cumulative protein deficit (cPD) over the first two weeks of life until the infant regains birth weight. However, there have been no clinical studies comparing the clinical and nutritional impact of these two strategies is unknown. Aims. The aims of this study were to quantify the amount of protein intake and to compare growth parameters at hospital discharge (as measured by discharge weight and head circumference percentiles) when using two different methodologies (BW vesrsus current daily weight until BW is regained) for calculating fluid and protein intake in the first two weeks after birth in ELBW infants. Methods. A retrospective review of infants weighing ≤ 1kg at birth was conducted from January 2005 to December 2009 (Phase 1; P1) and January 2012 to December 2014 (Phase 2; P2) in a tertiary care NICU. At this center, in P1 (2005-09) CW was exclusively used for calculating fluid, calorie, and protein administration till BW was regained. In P2 (2012-14), BW was exclusively used for all calculations. Both P1 and P2 periods were compared and analyzed for differences in demographics, nutritional intake, comorbid conditions, and growth outcomes. Results. We studied 146 infants with 84 and 62 infants in P1 and P2 periods, respectively. The mean gestational age was lower during Phase 1 (25.74 ±1.32 vs. 26.47 ±1.82 weeks. P value =0.01). However, the birth weights were not different between the two periods. When the multiple-regression analysis was done using a discharge weight of >10th percentile as the dependent variable, protein intake before regaining of BW (OR of 4.126 with 95th CI of 2.03-8.36, a P value of 0.00) and AGA status at birth (OR of 8.37 with 95th CI of 2.67-26.24) remained significant factors. Compared to P1, babies in P2 received 1g/kg/day more protein till BW was regained. In P1, 27% of babies who were appropriate for gestational age (AGA) for head circumference at birth became microcephalic by discharge, compared to 15.6% in P2 (p=0.03). Similarly, 75.3% of the babies who were AGA for weight at birth in P1 became small for gestational age (SGA) by discharge, compared to 16.7% in P2 (p=<0.0001). The number of days it took to regain BW was 9.6 days in P1 vs. 7 days in P2 (p=<0.0001). Conclusions. Basing nutrition calculations in ELBW on birth weight rather than current daily weight until the birth weight is regained resulted in significantly greater protein delivery, a significant decrease in the incidence of failure to thrive and smaller head circumference percentiles at discharge in ELBW infants.